Acute gestational cystitis (treatment characteristics) - Borovikov I.O; Kutsenko I.I; E.R. Rubinina; E.E. Gerasimenko; S.K. Betmen (LCC «Medicine-Inform», 2018)
Acute gestational cystitis (treatment characteristics) I.O. Borovikov, I.I. Kutsenko, E.R. Rubinina, E.E. Gerasimenko, S.K. Betmen Kuban State Medical University, Krasnodar, Russian Federation Aim: to evaluate the clinical experience of different options for the management of women with acute gestational cystitis. Patients and Methods: 96 female patients with acute gestational cystitis in the gestation period of 28-36 weeks, in whom uropathogenic microflora growth ≥105 CFU/ml was detected during urine culture, underwent a course of treatment, an analysis of which was conducted. Diagnosis of acute gestational cystitis was carried out on the basis of the clinical picture (acute onset, dysuria, pollakiuria, urinary urgency, incontinence and tenderness in the lower pelvic area, possible hematuria) and laboratory diagnostics (cito tests to detect bacteriuria and leukocyturia, clinical urine tests, Nechiporenko test, urine culture with flora and sensitivity to antibiotics). Assessment of a microbiota state of the urogenital tract was carried out using urine culture. Depending on the type of therapy, all pregnant women were divided into 3 groups: I (n=32) - treated with the drug fosfomycin trometamol; II (n=32) - cefuroxime axetil; III (n=32) - amoxicillin in combination with clavulanic acid. Prevention and treatment of concomitant vulvovaginal candidiasis was carried out by intravaginal applications of clotrimazole (2% cream). Results: the highest clinical and microbiological efficacy of treatment of acute gestational cystitis was found in the preparation containing fosfomycin trometamol (94.5%), with better compliance (among the adverse effects of drugs administration, respondents first of all noted the need of administration of cefuroxime axetil bis in day and amoxicillin in combination with clavulanic acid three times for five days, as well as a higher incidence of adverse effects when during the intake of these drugs). In group II and III, the efficacy of therapy was, respectively, 88.1 and 80.9%. As a concomitant antimycotic therapy, topical application of clotrimazole in the form of a vaginal cream (2%) has proven its effectiveness. Conclusion: fosfomycin trometamol (Fosfomycin Esparma) showed high clinical and microbiological efficacy in the treatment of acute gestational cystitis in the II and III trimester of pregnancy. Key words: acute gestational cystitis, vulvovaginal candidiasis, antibacterial therapy, uroseptics, antimycotics, fosfomycin trometamol. For citation: Borovikov I.O., Kutsenko I.I., Rubinina E.R. et al. Acute gestational cystitis (treatment characteristics). Russian Journal of Woman and Child Health. 2018;1(2):124-130.